Amplifying feedback loop between growth and wood anatomical characteristics of Fraxinus excelsior explains size-related susceptibility to ash dieback. (24th July 2020) - Klesse, Stefan; von Arx, Georg; Gossner, Martin M; Hug, Christian; Rigling, Andreas; Queloz, Valentin
Abstract: Since the 1990s the invasive fungus Hymenoscyphus fraxineus has caused severe crown dieback and high mortality rates in Fraxinus excelsior in Europe. In addition to a strong genetic control of tolerance to the fungus, previous studies have found landscape heterogeneity to be an additional driver of variability in the severity of dieback symptoms. However, apart from climatic conditions related to heat and humidity influencing fungal infection success, the mechanistic understanding of why smaller or slower-growing trees are more susceptible to dieback remains less well understood. Here, we analyzed three stands in Switzerland with a unique setting of 8 years of data availability of intra-annual diameter growth and annual crown health assessments. We complemented this by ring width and quantitative wood anatomical measurements extending back before the monitoring started to investigate if wood anatomical adjustments can help better explain the size-related dieback phenomenon. We found that slower-growing trees or trees with smaller crowns already before the arrival of the fungus were more susceptible to dieback and mortality. Defoliation directly reduced growth as well as maximum earlywood vessel size, and the positive relationship between vessel size and growth rate caused a positive feedback amplifying and accelerating crown dieback. Measured non-structural carbohydrate (NSC) concentrations in the outermost five rings did not significantly vary between healthy and weakened trees, which translate into large differences in absolute available amount of NSCs. Thus, we hypothesize that a lack of NSCs (mainly sugars) leads to lower turgor pressure and smaller earlywood vessels in the following year. This might impede efficient water transport and photosynthesis, and be responsible for stronger symptoms of dieback and higher mortality rates in smaller and slower-growing trees.